The Effects of Progressive Muscle Relaxation on Blood Pressure and Headache in Hypertension - Waruwu, Nona Kireina; Sembiring, Pinta Ulina; Kalesaran, Vinny Florensia; Manik, Marisa Junianti; Luturmas, Anthina Dorthea (STIKep PPNI Jawa Barat, 2023)
Aims: Hypertension is a condition of increased blood pressure that causes the heart to work harder to circulate blood throughout the body. Patients with hypertension more frequently complain of headaches. Progressive Muscle Relaxation (PMR) is a non-pharmacological treatment to overcome hypertension, headache symptoms, and maintain a deep relaxation state. Objective: The study aimed to determine PMR's effects on blood pressure and headache in hypertensive patients. Methods: This study utilized a quasi-experimental design with one group pretest and posttest design. A sample of 30 respondents with hypertension and headaches was obtained through convenience sampling. Data were then analyzed using paired t-test. Results: The results showed a decrease in blood pressure and headache intensity after administrated PMR. The number of respondents with stage 2 hypertension decreased from nine (30%) in the pretest to zero respondents (0%) in the posttest. There was a significant effect of giving PMR to clients with increased blood pressure accompanied by headaches (p-value of 0.000). Conclusion: PMR is a significant measure that can be used to reduce blood pressure and headache. It can be done independently from ten to 15 minutes daily for a more effective outcome. Therefore, it is suggested that clients with increased blood pressure can do the PMR exercise independently every day for 10-15 minutes to reduce blood pressure and headache intensity.